Quantifying the tradeoffs between different crop residue uses - Wijk, Mark T. van (International Livestock Research Institute, 2009)
During the December 2009 SLP meeting in Addis Ababa, Mark van Wijk (WUR) and colleagues presented some modelling work that could help quantify the tradeoffs between uses of crop residues - either incorporated in the soil to maintain soil fertility or fed to cattle. He emphasizes that the models help to quantify the consequences - 'what if' - of different decisions or strategies.